Evaluation of Anti-metastatic Effects of Ganoderma lucidum Extracts on Human Mammary Carcinoma Cell Line; MCF-7 - Ngakham, Jarunya (Thai Journal of Toxicology, 2017)
Ganoderma lucidum has been widely used as a traditional herbal medicine for promoting vitality and longevity in China and many Asian countries. It has been also used for the prevention or treatment of a variety of diseases including cancer. This study investigated the anti-cancer and anti-metastatic activities of methanol and water extracts from G. lucidum on breast cancer cell lines; MCF-7. The anti-cancer activity was determined with total protein determination method. The anti-invasion and anti-motility potential were evaluated using Matrigel-invasion assay and anti-motility assay, respectively. Semi-quantitative RT-PCR technique was performed to evaluated MMP-2 and MMP-9 mRNA expressions. The results showed the inhibitory effects of the methanol and water extracts from G. lucidum on the proliferation of MCF-7. The extracts have been also exhibited anti-metastatic activities by reducing the invasion and motility of MCF-7 in a dose-dependent manner. Moreover, these extracts down-regulated the function of MMP-2 and MMP-9 genes by decreasing the expression of MMP-9 mRNA and MMP-2 mRNA in treated breast cell line; MCF-7. In conclusion, all our findings indicated that the methanol and water extracts from G. lucidum possessed anti-cancer and anti-metastatic activities. They are promising for further investigation at cellular and molecular levels. In addition, further studies on pre-clinical and clinical are necessary for the validation of this herbal medicine in cancer prevention and treatment.